Human Resource Management Practices and Employee Satisfaction in the Banking Industry of Nepal - Khatri, Chudamani (Journal of Nepalese Management and Research, 2025)
This research aims to investigate the role of major Human Resource Management (HRM) practices: compensation, employee participation, grievance handling, training and development, and health and safety on job satisfaction among employees in the commercial banking industry of Nepal. The Banking industry is a crucial part of the Nepalese economy, and employee satisfaction is critical to the provision of quality services, productivity and organizational success. Determining the HRM practices that best affect job satisfaction can be of much help to managers who want to increase the commitment and performance of the workforce. There are various bodies of literature regarding the use of HRM practices in developed nations, but there is little empirical work on the HRM practices in the Nepalese socio-economic setting. To fill this gap in the research, the current study specifically targets the under-researched commercial banking industry. The survey was cross-sectional, and the sample comprised 440 employees in 14 commercial banks in Lumbini Province of Nepal. The hypothesized relationships between variables were tested using Smart PLS-SEM. The findings indicated that grievance handling was the only factor that had a significant and positive correlation with job satisfaction (p = 0.000), but no significant effects were found on compensation, employee participation, training and development, and health and safety. The results demonstrate that efficient grievance management plays an important role in promoting staff morale, and therefore, banks need to focus on good grievance-solving procedures as a strategy for improving employee morale and organizational peace.